Speaking of Online Learning: Alternative Practice-Based Learning Experiences for Speech Pathologists in Australia, Ghana and Hong Kong - Skeat, Jemma; Bampoe, Josephine Ohenewa; Booth, Susan; Brogan, Emily; Conway, Maya; Davenport, Rachel; Howells, Simone; Kan, Peggy; Krahe, Michelle; Hewat, Sally; Lewis, Abigail; Little, Alex; et al. (International Journal of Practice-based Learning in Health and Social Care, 2022)
<span class="NormalTextRun SCXW157708796 BCX9" data-ccp-parastyle="Keywords" data-ccp-parastyle-defn=""ObjectId":"a77a88f7-9c27-4ad3-9f2b-d0227acaf63a|206","ClassId":1073872969,"Properties":[469775450,"Keywords",201340122,"2",134234082,"true",134233614,"true",469778129,"Keywords",335572020,"1",134224900,"true",469777841,"Arial",469777842,"Arial",469777843,"Times New Roman",469777844,"Arial",469769226,"Arial,Times New Roman",268442635,"18",335559740,"240",201341983,"0",335559739,"200",469775498,"IJPBL Paragraph",469778324,"Normal",469778325,"["Subject codes"]"]">Speech Pathology programs usually send students to workplaces to learn clinical skills necessary for practice. During COVID-19, programs needed to respond quickly to ensure that students continued to gain the necessary experiences and skills required to progress through their program and graduate as clinicians, while simultaneously complying with COVID-19 requirements. Case studies from seven different universities in Australia, Ghana and Hong Kong described the diverse ways in which placements were adapted to be COVID-safe, taking into account local needs. Some practices which had been included in placement education prior to the pandemic, such as telepractice and simulation-based learning, were extended and developed during this time. Educators, students, clinicians and clients responded to the rapidly changing needs of the time with flexibility and innovation, utilising a variety of technologies and tools to support case-based and virtual learning opportunities. Feedback from these diverse stakeholders about the experiences was positive, despite inevitable limitations and less-than-ideal circumstances. The positive findings provided insights for consideration in the future: could strategies implemented in response to the pandemic continue to be incorporated into placement experiences, enhancing current practices and maintaining student performance outcomes? Exceptional circumstances prompted exceptional responses; flexibility and innovation were accelerated in response to the pandemic and may transform future placement-based learning opportunities.